2004
DOI: 10.1080/08927010410001662689
|View full text |Cite
|
Sign up to set email alerts
|

Antifouling Potential of Lubricious, Micro-engineered, PDMS Elastomers against Zoospores of the Green Fouling AlgaUlva (Enteromorpha)

Abstract: The settlement and release of Ulva spores from chemically modified, micro-engineered surface topographies have been investigated using poly(dimethyl siloxane) elastomers (PDMSe) with varying additions of non-network forming poly(dimethyl siloxane) based oils. The topographic features were based on 5 microns wide pillars or ridges separated by 5, 10, or 20 microns wide channels. Pattern depths were 5 or 1.5 microns. Swimming spores showed no marked difference in settlement on smooth surfaces covered with excess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
126
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(130 citation statements)
references
References 36 publications
3
126
0
1
Order By: Relevance
“…74 For instance, HoipkemeirerWilson and coworkers reported that topographically corrugated surfaces are capable of reducing biofouling. 75 The degree to which fouling was reduced was found to depend on the dimensions of the geometrical protrusions as well as the chemistry of the surfaces. Because biofouling includes a very diverse range of various species, whose sizes span several orders of magnitude, one single topographical pattern will not likely perform as an effective antifouling surface.…”
Section: What Are Wrinkles Good For Anyway?mentioning
confidence: 99%
“…74 For instance, HoipkemeirerWilson and coworkers reported that topographically corrugated surfaces are capable of reducing biofouling. 75 The degree to which fouling was reduced was found to depend on the dimensions of the geometrical protrusions as well as the chemistry of the surfaces. Because biofouling includes a very diverse range of various species, whose sizes span several orders of magnitude, one single topographical pattern will not likely perform as an effective antifouling surface.…”
Section: What Are Wrinkles Good For Anyway?mentioning
confidence: 99%
“…29 Silastic® brand silicone elastomers are biomaterials used in numerous medical devices including tubing, catheters, and pacemaker leads. The elastomer was prepared by mixing one part by weight of curing agent with ten parts by weight of resin, then degassing under vacuum ͑28-30 in.…”
Section: A Materialsmentioning
confidence: 99%
“…A number of investigations have explored the relationship between water contact angle and surface free energy of polymeric substrates with the settlement ͑attachment͒ and/or adhesion strength of various marine organisms. [15][16][17][18][19][20][21] Generally, for a wide range of organisms, there is a good correlation between low surface energy of the coating and enhanced fouling-release performance ͑i.e., low adhesion strength͒, although there are exceptions, notably for marine diatoms, which adhere more strongly to hydrophobic surfaces. 22 The green seaweed Ulva is the most common macroalgae that fouls man-made structures, including boats, buoys, ships, and submarines, and which reproduces by the production of vast numbers of microscopic motile spores ͑zoospores͒.…”
Section: Introductionmentioning
confidence: 99%